Preparation method and application of porous carbon material rich in carbon defects loaded with Fe single atom catalyst
By performing Joule heat treatment in a Joule heat rapid heating device and post-treatment method combined with aqueous hydrochloric acid solution, a porous carbon material loaded Fe single atom catalyst rich in carbon defects was prepared, which solved the problems of long reaction time, huge energy consumption and low single atom load in the traditional high-temperature calcination method, and achieved efficient preparation of the catalyst and excellent ORR catalytic performance.
Patent Information
- Application Number
- CN202411264332.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-10
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-09-10
AI Technical Summary
In the preparation of single-atom catalysts, the reaction time is long, the energy consumption is huge during the high-temperature calcination process, the single-atom load is low, and it is easy to aggregate and migrate, resulting in low catalytic activity and stability.
The preparation method of a porous carbon material loaded Fe single atom catalyst rich in carbon defects is adopted. By performing Joule heat treatment in a Joule heat rapid heating device, combined with the post-treatment method of hydrochloric acid aqueous solution, the pore structure and defects of the catalyst are regulated, and the conductivity and loading, dispersion and stability of Fe single atoms are improved.
The catalyst's electrical conductivity and electrical conductivity are improved, and it shows excellent performance in oxygen reduction reaction (ORR) and has high industrial prospects.
Smart Images

Figure CN118825304B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a preparation method and application of a porous carbon material rich in carbon defects loaded with Fe single atom catalyst, belonging to the technical field of single atom catalyst preparation and electrochemistry. Background Art
[0002] The development of new energy sources to replace fossil fuels is crucial to address the growing global energy demand and environmental issues. Hydrogen fuel is a promising way to store energy. It can be converted into electricity with high efficiency through direct electrochemical conversion in fuel cells, with only water as a byproduct. However, an important drawback of current fuel cell technology is the slow oxygen reduction reaction (ORR). Traditionally, ORR catalysts mainly use platinum (Pt) and its alloys as active materials, which are widely used due to their excellent activity and stability. However, the scarcity and high cost of platinum catalysts have seriously hindered the large-scale commercialization of proton exchange membrane fuel cells. Therefore, the development of alternative catalysts without platinum group metals (PGM) with high catalytic activity and good durability has become an important goal of current ORR research.
[0003] In recent years, single-atom catalysts have attracted much attention as a new type of ORR catalyst. Compared with traditional alloy or nanoparticle catalysts, single-atom catalysts have the largest surface atomic utilization rate, and each atom can participate in the catalytic reaction, thereby improving the catalytic efficiency. At present, the conventional preparation method of ORR single-atom catalysts is to fix metal single atoms on traditional carbon carriers by high-temperature calcination. This method not only consumes a lot of energy and takes a long time to prepare, but also the prepared single-atom catalyst has a low loading and is prone to aggregation and migration, which limits the improvement of its catalytic activity. Therefore, the development of a rapid, low-cost preparation method for high-loading, high-dispersion, and high-stability carbon-supported single-atom catalysts is not only of great significance for improving the performance of ORR catalysts, but also has a far-reaching impact on promoting the development and application of new energy technologies.
[0004] The Chinese invention patent document with publication number CN116426969A discloses a defective carbon-nitrogen skeleton-loaded single-atom iridium / iron-nickel catalyst and its preparation method and application. The invention first prepares a carbon skeleton by high-temperature pyrolysis of dicyandiamide, and then prepares a defective carbon skeleton by mixing with lithium chloride and isopropanol in turn through cumbersome processes such as ball milling, drying, heating, sulfuric acid treatment, deionized water washing, and drying. The prepared defective carbon skeleton is used as a carrier to adsorb metal ions to prepare a defective carbon-nitrogen skeleton-loaded single-atom catalyst. The defective carbon preparation method is cumbersome and inefficient, and does not involve the regulation of carbon pores.
[0005] The Chinese invention patent document with publication number CN117393782A discloses a non-precious metal single-atom ORR catalyst and its preparation method and application. The invention mixes polyacrylamide, a nitrogen source, a non-precious metal salt and deionized water and performs ball milling, then freeze-dries to obtain a freeze-dried mixture, and then calcines the freeze-dried mixture in an inert gas in a segmented manner, and finally treats the calcined product with acid to obtain a non-precious metal single-atom ORR catalyst. This method adopts the traditional distributed calcination method, which requires insulation in an inert gas at 500-600°C and 750-950°C for 2h, respectively, and the heating rate does not exceed 6°C / min. The catalyst preparation efficiency is low and the energy consumption is high. In addition, the catalyst carrier does not involve the regulation of pores and defects.
[0006] The Chinese invention patent document with announcement number CN114471520A discloses a ZIF-8-based porous carbon material and its preparation method and application. The invention first prepares a ZIF-8 material loaded with a metal salt by a solvothermal method, and then pyrolyzes it at 600-900°C in a tubular furnace for 1-5 hours to obtain a ZIF-8-based porous carbon material. This method utilizes the activation effect of the pyrolysis product and the catalytic effect of the loaded metal salt during the pyrolysis process to construct a microporous-mesoporous multi-level pore structure. Under normal circumstances, the ligand of ZIF-8 has been completely decomposed after 600°C, and no gas with pore-forming function is produced. The structure of the carbon material can only be limitedly regulated by metal, which limits the further improvement of the pore structure of the carbon material. In addition, this preparation method is time-consuming and energy-consuming and does not involve the regulation of carbon material defects. Summary of the invention
[0007] The purpose of the present invention is to provide a method for preparing a porous carbon material rich in carbon defects loaded with Fe single atom catalyst, which can solve the problems of long reaction time, huge energy consumption, low single atom loading, easy aggregation and migration, low catalyst activity and stability in the process of high-temperature calcination to prepare the catalyst, can improve the electrical conductivity and conductive properties of the catalyst, show excellent performance in the oxygen reduction reaction (ORR), and has broad industrial prospects.
[0008] To achieve this object, the technical solution of the present invention is:
[0009] The present invention provides a method for preparing a porous carbon material rich in carbon defects supported Fe single atom catalyst, comprising the following steps:
[0010] (1) dissolving zinc nitrate, ferric nitrate and calcium chloride in methanol to obtain a first mixed solution; dissolving 2-methylimidazole in methanol to obtain a second mixed solution;
[0011] (2) After the first mixed solution and the second mixed solution are evenly mixed, ultrasonic reaction is carried out at room temperature for 6-12 hours, and then centrifugation and vacuum drying are performed to obtain a first precursor;
[0012] (3) adding the first precursor into deionized water to obtain a third mixed solution, adding the sodium carbonate aqueous solution dropwise into the stirred third mixed solution, and then stirring the mixture at room temperature for 1-3 hours, centrifuging, washing, and vacuum drying to obtain a second precursor;
[0013] (4) grinding the second precursor into powder, placing the second precursor powder in a groove of a graphite sample stage of a Joule heat rapid heating device, and performing Joule heat treatment under a nitrogen protective atmosphere to obtain a third precursor;
[0014] (5) Add the third precursor to a hydrochloric acid aqueous solution, stir and heat the reaction at 60-80° C. for 12-18 h, and obtain a porous carbon material rich in carbon defects loaded with Fe single atom catalyst through centrifugation, washing, and vacuum drying.
[0015] Furthermore, in the step (1), the ratio of zinc nitrate, ferric nitrate, calcium chloride and methanol in the first mixed solution is: 1mmol:0.3-0.5mmol:0.1-0.3mmol:20mL; the ratio of 2-methylimidazole and methanol in the second mixed solution is: 4-8mmol:20mL.
[0016] Furthermore, in step (2), the vacuum drying conditions are: drying temperature 50-80°C, and drying time 18-24h.
[0017] Furthermore, in the step (3), the ratio of the first precursor to deionized water in the third mixed solution is 1.2-8.4 g:20 mL; the amount of the sodium carbonate aqueous solution added is 0.5-3 mL:1 mL based on the amount of deionized water in the third mixed solution; and the concentration of the sodium carbonate aqueous solution is 0.05-1 g / mL.
[0018] Furthermore, in steps (3) and (5), the washing conditions are: washing with deionized water three to five times; and the vacuum drying conditions are: drying temperature 80-100° C., and drying time 18-24 h.
[0019] Furthermore, in step (4), the conditions of Joule heat treatment are: heat treatment temperature 600-2000°C, heating rate 1000-4000°C / s, and Joule heat treatment times 3-10 times. Joule heat treatment is heating from room temperature to the target temperature and then naturally cooling to room temperature, which is represented as one time.
[0020] Furthermore, in step (5), the concentration of the hydrochloric acid aqueous solution is 1-2M; and the usage ratio of the third precursor to the hydrochloric acid aqueous solution is 0.2-0.5g:50mL.
[0021] Another object of the present invention is to provide an application of a carbon defect-rich porous carbon material prepared by the above method and loaded with Fe single atom catalyst, which is used as an electrochemical catalyst for oxygen reduction reaction (ORR) in alkaline electrolyte.
[0022] The beneficial effects of the present invention are:
[0023] (1) Compared with the traditional high-temperature calcination method, the Joule heat treatment technology of the present invention has simple equipment operation, high catalyst preparation efficiency, low energy consumption, and helps to inhibit the collapse of the pore structure under high temperature; at the same time, the extreme environment caused by rapid heating gives the material a large number of defects, while extremely rapid cooling can largely retain these defects.
[0024] (2) The present invention uses calcium carbonate generated during the in-situ chemical reaction as a structural modifier and combines it with Joule heat treatment technology to enrich the pore structure and defects of the catalyst, thereby improving the conductivity of the catalyst and the loading, dispersion and stability of Fe single atoms on the carbon carrier. By utilizing the rapid heating and cooling characteristics of Joule heat treatment technology, the precursor can reach a high temperature instantly and then cool and solidify rapidly. Due to this rapid heating and cooling characteristic, the Fe element in the precursor does not have enough time to undergo significant aggregation, which is beneficial to increase the loading of single atoms.
[0025] (3) The post-treatment method of the hydrochloric acid aqueous solution of the present invention not only helps to remove excess calcium carbonate, but also helps to form mesopores and macropores. The removal of calcium carbonate helps to improve the conductivity, and the multi-level pore structure of mesopores and macropores helps to desorb oxygen products, which together improves the electrochemical catalytic effect. In addition, the use of hydrochloric acid aqueous solution in combination with Joule heat treatment technology has a synergistic effect and has a better pore-forming effect.
[0026] (4) Application of the porous carbon material rich in carbon defects in the present invention to Fe single-atom catalysts. Since the catalyst has a multi-level pore structure and abundant carbon defect sites, it not only provides high-density fixation of single-atom Fe on the carrier and inhibits the aggregation of single-atom Fe, but also provides convenient conditions for the adsorption and dissociation of oxygen molecules during the ORR reaction, further improving the catalytic efficiency. Its specific surface area, pore size range, half-wave potential, limiting current density, carbon defect structure (I D / I G ) content reached 1123.57-1280.65m 2 / g, 1-80nm, 0.85-0.92V, 5.16-5.38mA / cm 2、0.935-1.012. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 The specific surface area test diagram of nitrogen total adsorption (N2-BET) of the porous carbon material loaded with Fe single atom catalyst (PDC / Fe0.12-1200) rich in carbon defects obtained in step (5) of Example 1, wherein the specific surface area test result is derived from the N2-BET test result at 77K;
[0028] Figure 2 This is the NLDFT model full pore distribution test diagram of PDC / Fe0.12-1200 obtained in step (5) of Example 1, wherein the NLDFT model full pore distribution test result is derived from the N2-BET test result;
[0029] Figure 3 The Raman spectrum of PDC / Fe0.12-1200 obtained in step (5) of Example 1;
[0030] Figure 4 This is a spherical aberration corrected transmission electron microscopy image of PDC / Fe0.12-1200 obtained in step (5) of Example 1;
[0031] Figure 5 This is a test graph of the oxygen reduction reaction (ORR) catalytic performance of PDC / Fe0.12-1200 obtained in step (5) of Example 1. DETAILED DESCRIPTION
[0032] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments so that a person skilled in the art can better understand and implement the present invention, but the protection scope of the present invention is not limited thereto.
[0033] Unless otherwise specified, the raw materials used in the embodiments of the present invention are all commercially available materials; unless otherwise specified, all technical and scientific terms used in the present invention have the same meanings as those generally understood by those skilled in the art.
[0034] In a specific embodiment of the present invention, the Joule heat rapid heating device used is composed of a gas circuit device, a vacuum pump, a graphite sample stage, a temperature control system, and a data acquisition system. The model is CIS-JH3.3-P, the output voltage is 0-40V, the output current is 0-500A, the temperature measurement range is 0-3000℃, the power supply is 380V / 30A, and the current ramp time is 1ms. Example 1
[0035] (1) Add 10 mmol zinc nitrate, 4 mmol iron nitrate, and 2 mmol calcium chloride to 200 mL methanol, and ultrasonicate for 1.5 h to obtain a first mixed solution; add 60 mmol 2-methylimidazole to 200 mL methanol, and ultrasonicate for 8 min to obtain a second mixed solution;
[0036] (2) After the first mixed solution and the second mixed solution are evenly mixed, ultrasonic reaction is carried out at room temperature for 10 hours, and then centrifugation and vacuum drying are carried out at 70° C. for 22 hours to obtain a first precursor;
[0037] (3) 4.2 g of the first precursor was added to 20 mL of deionized water to obtain a third mixed solution, 30 mL of a 0.08 g / mL sodium carbonate aqueous solution was added dropwise to the third mixed solution under stirring, and then stirred at room temperature for 2 h, centrifuged, washed with deionized water four times, and vacuum dried at 90 ° C for 22 h to obtain a second precursor;
[0038] (4) Grinding the second precursor into powder, placing 0.5 g of the second precursor powder in the groove of the graphite sample stage of the Joule heat rapid heating device, and then performing Joule heat treatment 6 times under a nitrogen protective atmosphere, with the Joule heat treatment temperature of 1200°C and the Joule heat treatment heating rate of 3000°C / s, to obtain a third precursor;
[0039] (5) 0.3 g of the third precursor was added to 50 mL of 1.5 M hydrochloric acid aqueous solution, and the mixture was stirred and heated at 70 °C for 15 h. The mixture was centrifuged, washed four times with deionized water, and vacuum dried at 90 °C for 22 h to obtain a porous carbon material rich in carbon defects loaded with Fe single atom catalyst, named PDC / Fe0.12-1200.
[0040] The carbon defect-rich porous carbon material supported Fe single atom catalyst (PDC / Fe0.12-1200) obtained in step (5) was subjected to nitrogen full adsorption (N2-BET) specific surface area and NLDFT model full pore distribution test, Raman spectroscopy test, and spherical aberration corrected transmission electron microscopy test. The test results are shown in Figure 1 , Figure 2 , Figure 3 , Figure 4 .
[0041] Depend on Figure 1 It can be seen that the N2-BET specific surface area test of PDC / Fe0.12-1200 has a clearly visible hysteresis loop, indicating that the material has a rich mesoporous structure and a large specific surface area of 1123.57 m² / g; Figure 2It can be seen that PDC / Fe0.12-1200 has abundant micropores, mesopores and macropores with a pore size range of 1-80 nm. The multi-level pore structure improves the mass transfer process in ORR catalysis and enhances the ORR catalytic activity. Figure 3 It can be seen that I D / I G The ratio is the D band (1353 cm -1 peaks around 1587 cm) and ordered sp2 hybridized carbon G band (1587 cm -1 ) peak area ratio, PDC / Fe0.12-1200 I D / I G The value of I is 1.012. D / I G is much larger than 0.6 (conventional materials), indicating that PDC / Fe0.12-1200 has a rich carbon defect structure; Figure 4 It can be seen that the metal single atoms in PDC / Fe0.12-1200 are uniformly distributed on the carrier.
[0042] The porous carbon material rich in carbon defects obtained in step (5) loaded with Fe single atom catalyst, namely PDC / Fe0.12-1200, is applied to oxygen reduction reaction (ORR) under alkaline conditions, comprising the following application steps:
[0043] 2 mg of PDC / Fe0.12-1200 was dispersed in a mixed solvent (the mixed solvent consisted of 0.45 mL of isopropanol, 0.5 mL of deionized water, and 50 μL of 0.5% Nafion solution). After ultrasonic treatment for 2 h, a PDC / Fe0.12-1200 mixed solution was obtained. The PDC / Fe0.12-1200 mixed solution was drop-coated on a glassy carbon electrode using a pipette. The loading amount of PDC / Fe0.12-1200 on the glassy carbon electrode was 0.4 mg / cm 2 After natural air drying, a PDC / Fe0.12-1200 modified glassy carbon electrode was obtained; the electrochemical test was carried out on a PINE rotating disk ring electrode device (AFMSSRCE) and a CHI760E electrochemical workstation, and a three-electrode test system was used for ORR catalytic performance test, where the rotation speed of the PINE rotating disk ring electrode device was 1600rpm, the linear voltammetric scanning rate was 5mV / s, and the test reaction liquid was 0.1M KOH. Among them, the ORR catalytic performance test included a linear sweep voltammetric (LSV) test and a cycle stability test. The test results are shown in Figure 5 .
[0044] As shown in Table 1, under alkaline conditions, the half-wave potentials of PDC / Fe0.12-1200 prepared in Example 1 and commercial Pt / C materials reached 0.92 V and 0.85 V, respectively, and the limiting current densities were 5.16 mA / cm 2 and 5.15mA / cm 2 PDC / Fe0.12-1200 exhibits ORR catalytic performance that is superior to that of commercial Pt / C materials and has broad prospects for industrial application. After 5000 cycles of continuous use of PDC / Fe0.12-1200, the half-wave potential only decreases by 6 mV, indicating that PDC / Fe0.12-1200 has good stability. Example 2
[0045] (1) Add 10 mmol zinc nitrate, 3 mmol iron nitrate, and 1 mmol calcium chloride to 200 mL methanol, and ultrasonicate for 1.0 h to obtain a first mixed solution; add 40 mmol 2-methylimidazole to 200 mL methanol, and ultrasonicate for 5 min to obtain a second mixed solution;
[0046] (2) After the first mixed solution and the second mixed solution are evenly mixed, ultrasonic reaction is carried out at room temperature for 6 hours, and then centrifugation and vacuum drying are carried out at 50° C. for 24 hours to obtain a first precursor;
[0047] (3) 1.2 g of the first precursor was added to 20 mL of deionized water to obtain a third mixed solution, 10 mL of a 1 g / mL sodium carbonate aqueous solution was added dropwise to the third mixed solution under stirring, and then stirred at room temperature for 1 h, centrifuged, washed three times with deionized water, and vacuum dried at 80 ° C for 24 h to obtain a second precursor;
[0048] (4) Grinding the second precursor into powder, placing 0.5 g of the second precursor powder in the groove of the graphite sample stage of the Joule heat rapid heating device, and then performing Joule heat treatment three times under a nitrogen protective atmosphere, with the Joule heat treatment temperature of 2000°C and the Joule heat treatment heating rate of 4000°C / s, to obtain a third precursor;
[0049] (5) 0.2 g of the third precursor was added to 50 mL of 1 M hydrochloric acid aqueous solution, and the mixture was stirred and heated at 60 °C for 18 h. The mixture was centrifuged, washed three times with deionized water, and vacuum dried at 80 °C for 24 h to obtain a porous carbon material rich in carbon defects loaded with Fe single atom catalyst, named PDC / Fe0.02-2000.
[0050] The carbon defect-rich porous carbon material loaded with Fe single atom catalyst (PDC / Fe0.02-2000) obtained in step (5) was subjected to N2-BET specific surface area and NLDFT model full pore distribution test and Raman spectrum test, respectively. The test results are shown in Table 1.
[0051] As shown in Table 1, the N2-BET specific surface area test and NLDFT model full pore distribution test of PDC / Fe0.02-2000 show that the material has a large specific surface area and a multi-level pore structure. The specific surface area is 1280.65 m² / g, and the pore size distribution is 1-60nm (micropore, mesopore, macropore structure). The multi-level pore structure improves the mass transfer process in ORR catalysis and enhances the ORR catalytic activity. In the Raman spectrum test, due to I D / I G The value of 0.935 is much larger than 0.6 (conventional materials), indicating that PDC / Fe0.02-2000 has a rich carbon defect structure.
[0052] The carbon defect-rich porous carbon material loaded with Fe single atom catalyst (PDC / Fe0.02-2000) obtained in step (5) was applied to the ORR performance application test under alkaline conditions. The method of the ORR performance application test was the same as that of Example 1. The test results are shown in Table 1.
[0053] As shown in Table 1, the half-wave potential of PDC / Fe0.02-2000 and commercial Pt / C materials are both 0.85 V, and the limiting current density is 5.38 mA / cm 2 and 5.15mA / cm 2 The above results show that PDC / Fe0.02-2000 exhibits ORR catalytic performance close to that of commercial Pt / C materials and has prospects for industrial application. Example 3
[0054] (1) Add 10 mmol zinc nitrate, 5 mmol iron nitrate, and 3 mmol calcium chloride to 200 mL methanol, and ultrasonicate for 2.0 h to obtain a first mixed solution; add 80 mmol 2-methylimidazole to 20 mL methanol, and ultrasonicate for 10 min to obtain a second mixed solution;
[0055] (2) After the first mixed solution and the second mixed solution are evenly mixed, ultrasonic reaction is carried out at room temperature for 12 hours, and then centrifugation and vacuum drying are carried out at 80° C. for 18 hours to obtain a first precursor;
[0056] (3) 8.4 g of the first precursor was added to 20 mL of deionized water to obtain a third mixed solution, 60 mL of a 0.05 g / mL sodium carbonate aqueous solution was added dropwise to the third mixed solution under stirring, and then stirred at room temperature for 3 h, centrifuged, washed with deionized water five times, and vacuum dried at 100 ° C for 18 h to obtain a second precursor;
[0057] (4) Grinding the second precursor into powder, placing 0.5 g of the second precursor powder in the groove of the graphite sample stage of the Joule heat rapid heating device, and then performing Joule heat treatment 10 times under a nitrogen protective atmosphere, with the Joule heat treatment temperature of 600°C and the Joule heat treatment heating rate of 1000°C / s, to obtain a third precursor;
[0058] (5) 0.5 g of the third precursor was added to 50 mL of 2 M hydrochloric acid aqueous solution, and the mixture was stirred and heated at 80 °C for 12 h. The mixture was centrifuged, washed with deionized water five times, and vacuum dried at 100 °C for 18 h to obtain a porous carbon material rich in carbon defects loaded with Fe single atom catalyst, named PDC / Fe2.5-600.
[0059] The carbon defect-rich porous carbon material loaded with Fe single atom catalyst (PDC / Fe2.5-600) obtained in step (5) was subjected to N2-BET specific surface area and NLDFT model full pore distribution test and Raman spectrum test, and the test results are shown in Table 1.
[0060] As shown in Table 1, the N2-BET specific surface area test and NLDFT model full pore distribution test of PDC / Fe2.5-600 show that the material has a large specific surface area and a multi-level pore structure. The specific surface area is 1200.46 m² / g, and the pore size distribution is 1-70nm (micropore, mesopore, macropore structure). The multi-level pore structure improves the mass transfer process in ORR catalysis and enhances the ORR catalytic activity. In the Raman spectrum test, due to I D / I G It is 0.984, which is much larger than 0.6 (conventional materials), indicating that PDC / Fe2.5-600 has a rich carbon defect structure.
[0061] The carbon defect-rich porous carbon material loaded with Fe single atom catalyst (PDC / Fe2.5-600) obtained in step (5) was applied to the ORR performance application test under alkaline conditions. The method of the ORR performance application test was the same as that of Example 1. The test results are shown in Table 1.
[0062] As shown in Table 1, the half-wave potentials of PDC / Fe2.5-600 and commercial Pt / C materials are 0.89 V and 0.85 V, respectively, and the limiting current densities are 5.25 mA / cm 2 and 5.15mA / cm 2 The above results show that PDC / Fe2.5-600 exhibits ORR catalytic performance close to that of commercial Pt / C materials and has prospects for industrial application. Example 4
[0063] (1) Add 10 mmol zinc nitrate, 3.5 mmol iron nitrate, and 1.5 mmol calcium chloride to 200 mL methanol, and ultrasonicate for 1.5 h to obtain a first mixed solution; add 70 mmol 2-methylimidazole to 200 mL methanol, and ultrasonicate for 8 min to obtain a second mixed solution;
[0064] (2) After the first mixed solution and the second mixed solution are evenly mixed, ultrasonic reaction is carried out at room temperature for 10 hours, and then centrifugation and vacuum drying are carried out at 70° C. for 22 hours to obtain a first precursor;
[0065] (3) 4.2 g of the first precursor was added to 20 mL of deionized water to obtain a third mixed solution, 40 mL of a 0.07 g / mL sodium carbonate aqueous solution was added dropwise to the third mixed solution under stirring, and then stirred at room temperature for 2 h, centrifuged, washed with deionized water four times, and vacuum dried at 90 ° C for 22 h to obtain a second precursor;
[0066] (4) Grinding the second precursor into powder, placing 0.5 g of the second precursor powder in the groove of the graphite sample stage of the Joule heat rapid heating device, and then performing Joule heat treatment 7 times under a nitrogen protective atmosphere, with the Joule heat treatment temperature of 1500°C and the Joule heat treatment heating rate of 3000°C / s, to obtain a third precursor;
[0067] (5) 0.3 g of the third precursor was added to 50 mL of 1.2 M hydrochloric acid aqueous solution, and the mixture was stirred and heated at 70 °C for 15 h. The mixture was centrifuged, washed four times with deionized water, and vacuum dried at 90 °C for 22 h to obtain a carbon defect-rich porous carbon material loaded with Fe single atom catalyst, which was named PDC / Fe1.6-1500.
[0068] The carbon defect-rich porous carbon material loaded with Fe single atom catalyst (PDC / Fe1.6-1500) obtained in step (5) was subjected to N2-BET specific surface area and NLDFT model full pore distribution test and Raman spectrum test, respectively. The test results are shown in Table 1.
[0069] As shown in Table 1, the N2-BET specific surface area test and NLDFT model full pore distribution test of PDC / Fe1.6-1500 show that the material has a large specific surface area and a multi-level pore structure. The specific surface area is 1180.56 m² / g, and the pore size distribution is 1-75nm (micropore, mesopore, macropore structure). The multi-level pore structure improves the mass transfer process in ORR catalysis and enhances the ORR catalytic activity. In the Raman spectrum test, due to I D / I G The value of 0.999 is much larger than 0.6 (conventional materials), indicating that PDC / Fe2.5-600 has a rich carbon defect structure.
[0070] The carbon defect-rich porous carbon material loaded with Fe single atom catalyst (PDC / Fe1.6-1500) obtained in step (5) was applied to the ORR performance application test under alkaline conditions. The method of the ORR performance application test was the same as that of Example 1. The test results are shown in Table 1.
[0071] As shown in Table 1, the half-wave potentials of PDC / Fe1.6-1500 and commercial Pt / C materials are 0.90 V and 0.85 V, respectively, and the limiting current densities are 5.20 mA / cm 2 and 5.15mA / cm 2 The above results show that PDC / Fe1.6-1500 exhibits ORR catalytic performance close to that of commercial Pt / C materials and has prospects for industrial application. Comparative Example 1
[0072] The difference between Comparative Example 1 and Example 1 is that no calcium chloride is added in step (1), and the other steps remain unchanged.
[0073] The carbon defect-rich porous carbon material loaded with Fe single atom catalyst obtained in step (5) was subjected to N2-BET specific surface area and NLDFT model full pore distribution test and Raman spectrum test, and the test results are shown in Table 1.
[0074] As shown in Table 1, without the addition of calcium chloride, the specific surface area and pore size range of the Fe single atom catalyst supported by the porous carbon material rich in carbon defects in Comparative Example 1 and the I D / I G 1080.32 m 2 / g, 1-40nm (micropores, mesoporous structure), and 0.695, which are much lower than the test results of Example 1. It can be seen that calcium chloride not only affects the specific surface area and pore size distribution, but also affects the structural content of carbon defects.
[0075] The porous carbon material rich in carbon defects obtained in step (5) and loaded with Fe single atom catalyst was applied to an ORR performance application test under alkaline conditions. The method for the ORR performance application test was the same as that in Example 1. The test results are shown in Table 1.
[0076] As shown in Table 1, the half-wave potentials of the carbon defect-rich porous carbon material loaded with Fe single atom catalyst and the commercial Pt / C material in Comparative Example 1 reached 0.65 V and 0.85 V, respectively, and the limiting current density was 5.63 mA / cm 2 , 5.15mA / cm 2, indicating that the ORR catalytic performance of the Fe single-atom catalyst loaded on the porous carbon material rich in carbon defects in Comparative Example 1 is far lower than that of the commercial Pt / C material. Therefore, the addition of calcium chloride affects the specific surface area and pore size distribution (multi-level pore structure) and carbon defect structure, and thus affects the catalytic performance. The addition of calcium chloride is a key factor. Comparative Example 2
[0077] The difference between Comparative Example 2 and Example 1 is that the heating device and heating conditions in step (4) are different, and the other steps remain unchanged. The specific operation is as follows:
[0078] The second precursor was ground into powder, and then 0.5 g of the second precursor powder was placed in a muffle furnace, and then calcined under a nitrogen protective atmosphere at a calcination temperature of 1200° C., a heating rate of 5° C. / min, and a heat preservation reaction for 2 hours to obtain a third precursor.
[0079] The carbon defect-rich porous carbon material loaded with Fe single atom catalyst obtained in step (5) was subjected to N2-BET specific surface area and NLDFT model full pore distribution test and Raman spectrum test, and the test results are shown in Table 1.
[0080] As shown in Table 1, under the calcination conditions in the muffle furnace, the specific surface area and pore size range of the Fe single atom catalyst supported by the porous carbon material rich in carbon defects in Comparative Example 2 and the I D / I G 1030.52 m 2 / g, 1-65nm (micropore, mesopore, macropore structure), 0.683, which are much lower than the test results of Example 1. It can be seen that the heating device not only affects the specific surface area and pore size distribution, but also affects the structural content of carbon defects.
[0081] The porous carbon material rich in carbon defects obtained in step (5) and loaded with Fe single atom catalyst was applied to an ORR performance application test under alkaline conditions. The method for the ORR performance application test was the same as that in Example 1. The test results are shown in Table 1.
[0082] As shown in Table 1, the half-wave potentials of the carbon defect-rich porous carbon material loaded with Fe single atom catalyst and the commercial Pt / C material in Comparative Example 2 reached 0.68 V and 0.85 V, respectively, and the limiting current density was 5.65 mA / cm 2 , 5.15mA / cm 2 , indicating that the ORR catalytic performance of the Fe single atom catalyst loaded on the porous carbon material rich in carbon defects in Comparative Example 2 is far lower than that of the commercial Pt / C material. Therefore, the use of a heating device has different effects on the specific surface area and pore size distribution (multi-level pore structure) of the catalyst and the carbon defect structure, which in turn affects the catalytic performance. The Joule heat rapid heating device is another key factor. Comparative Example 3
[0083] The difference between Comparative Example 3 and Example 1 is that the calcium source in step (1) is different, and calcium chloride is replaced by calcium carbonate.
[0084] The carbon defect-rich porous carbon material loaded with Fe single atom catalyst obtained in step (5) was subjected to N2-BET specific surface area and NLDFT model full pore distribution test and Raman spectrum test, and the test results are shown in Table 1.
[0085] As shown in Table 1, the specific surface area and pore size range of the Fe single atom catalyst supported by the porous carbon material rich in carbon defects in Comparative Example 3 and the I D / I G 1100.72 m 2 / g, 1-70nm (micropore, mesopore, macropore structure), 0.883, which are much lower than the test results of Example 1. It can be seen that the effect of directly adding calcium carbonate to the reaction is much lower than that of calcium carbonate produced in the in-situ chemical reaction process.
[0086] The porous carbon material rich in carbon defects obtained in step (5) and loaded with Fe single atom catalyst was applied to an ORR performance application test under alkaline conditions. The method for the ORR performance application test was the same as that in Example 1. The test results are shown in Table 1.
[0087] As shown in Table 1, the half-wave potentials of the carbon defect-rich porous carbon material loaded with Fe single atom catalyst and the commercial Pt / C material in Comparative Example 3 reached 0.75 V and 0.85 V, respectively, and the limiting current density was 5.55 mA / cm 2 , 5.15mA / cm 2 , indicating that the ORR catalytic performance of the Fe single-atom catalyst loaded on the porous carbon material rich in carbon defects in Comparative Example 3 is far lower than that of the commercial Pt / C material. Therefore, the calcium carbonate produced during the in-situ chemical reaction affects the specific surface area, pore size range, and carbon defect structure content of the catalyst, thereby affecting the catalytic effect.
[0088]
[0089] I D / I G : The peak intensity ratio of the D band of disordered carbon structure and the G band of ordered sp2 hybridized carbon in the Raman spectrum.
[0090] By comparing Comparative Example 1 with Examples 1-4, it can be seen that the addition of calcium chloride affects the specific surface area and pore size distribution (multi-level pore structure) and carbon defect structure, thereby affecting the catalytic performance. The larger the half-wave potential and the smaller the limiting current, the better the ORR performance. It can be seen that the addition of calcium chloride is a key factor in the preparation of the catalyst. By comparing Comparative Example 2 with Examples 1-4, it can be seen that the performance of the catalyst prepared by the traditional muffle furnace method is significantly inferior to that of the catalyst prepared by using in-situ chemical synthesis of CaCO3 additives combined with Joule heat treatment technology. This is mainly because the CaCO3 additive generated in situ during the high-temperature calcination process will release a large amount of CO2, inhibiting the agglomeration of carbon materials at high temperatures, promoting the formation of a multi-level pore structure, and significantly increasing the specific surface area of the catalyst; Joule heat treatment technology has the characteristics of rapid heating and cooling, which will inhibit the shrinkage (collapse) of the catalyst pores and the agglomeration of metal atoms, and is beneficial to the modification of the catalyst by CO2 and CaO, further generating carbon defects and enriching the multi-level pore structure; these defects and multi-level pore structures help to stabilize Fe single atoms, inhibit their aggregation, improve the utilization rate and stability of Fe single atoms in the ORR catalytic reaction, and also provide convenient conditions for the adsorption and dissociation of oxygen molecules during the ORR reaction. Combined with the conductivity of the porous carbon material, the catalytic efficiency is further improved, showing excellent ORR catalytic performance. Comparing Comparative Example 3 with Examples 1-4, it can be seen that the in-situ chemically synthesized CaCO3 is better than the direct addition method. This is mainly because the in-situ chemically synthesized CaCO3 combined with the Joule heat treatment technology has a greater influence on the specific surface area, pore size range, and carbon defect structure content of the catalyst, thereby achieving a good electrochemical effect.
[0091] The above embodiments are intended to illustrate the essential content of the present invention, but are not intended to limit the protection scope of the present invention. Those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and protection scope of the technical solution of the present invention.
Claims
1. A method for preparing a porous carbon material rich in carbon defects supported Fe single atom catalyst, characterized in that: The following steps are involved: (1) dissolving zinc nitrate, ferric nitrate and calcium chloride in methanol to obtain a first mixed solution; Dissolving 2-methylimidazole in methanol to obtain a second mixed solution; (2) After the first mixed solution and the second mixed solution are uniformly mixed, ultrasonic reaction is carried out at room temperature for 6-12 hours, and then centrifugation and vacuum drying are performed to obtain a first precursor; (3) adding the first precursor into deionized water to obtain a third mixed solution, adding the sodium carbonate aqueous solution dropwise into the stirred third mixed solution, and then stirring the mixture at room temperature for 1-3 hours, centrifuging, washing, and vacuum drying to obtain a second precursor; (4) grinding the second precursor into powder, placing the second precursor powder in a groove of a graphite sample stage of a Joule heat rapid heating device, and performing Joule heat treatment under a nitrogen protective atmosphere to obtain a third precursor; (5) adding the third precursor to a hydrochloric acid aqueous solution, stirring and heating the mixture at 60-80° C. for 12-18 h, centrifuging, washing, and vacuum drying to obtain a porous carbon material rich in carbon defects and loaded with Fe single atom catalyst; In the step (4), the conditions of the Joule heat treatment are: heat treatment temperature 600-2000°C, heating rate 1000-4000°C / s, and Joule heat treatment times 3-10 times.
2. The method for preparing a porous carbon material rich in carbon defects supported Fe single atom catalyst according to claim 1, characterized in that: In the step (1), the ratio of zinc nitrate, ferric nitrate, calcium chloride and methanol in the first mixed solution is: 1mmol: 0.3-0.5mmol: 0.1-0.3mmol: 20mL; The usage ratio of 2-methylimidazole and methanol in the second mixed solution is: 4-8mmol:20mL.
3. The method for preparing a porous carbon material rich in carbon defects supported Fe single atom catalyst according to claim 1, characterized in that: In the step (2), the vacuum drying conditions are: drying temperature 50-80°C, and drying time 18-24h.
4. The method for preparing a porous carbon material rich in carbon defects supported Fe single atom catalyst according to claim 1, characterized in that: In the step (3), the ratio of the first precursor to deionized water in the third mixed solution is 1.2-8.4 g:20 mL; the amount of the sodium carbonate aqueous solution added is 0.5-3 mL:1 mL based on the amount of deionized water in the third mixed solution; and the concentration of the sodium carbonate aqueous solution is 0.05-1 g / mL.
5. The method for preparing a porous carbon material rich in carbon defects supported Fe single atom catalyst according to claim 1, characterized in that: In the steps (3) and (5), the washing conditions are: washing with deionized water for three to five times; and the vacuum drying conditions are: drying temperature 80-100° C., and drying time 18-24 h.
6. The method for preparing a porous carbon material rich in carbon defects supported Fe single atom catalyst according to claim 1, characterized in that: In the step (5), the concentration of the hydrochloric acid aqueous solution is 1-2M; the dosage ratio of the third precursor to the hydrochloric acid aqueous solution is 0.2-0.5g:50mL.
7. An application of a porous carbon material rich in carbon defects prepared by the preparation method according to any one of claims 1 to 6 to support Fe single atom catalyst, characterized in that: It is used as an electrochemical catalyst for oxygen reduction reaction in alkaline electrolyte.
Citation Information
Patent Citations
ZIF-8-based porous carbon material as well as preparation method and application thereof
CN114471520A
Defected carbon-nitrogen skeleton loaded monatomic iridium / iron-nickel catalyst and preparation method and application thereof
CN116426969A
Non-noble metal monatomic ORR catalyst as well as preparation method and application thereof
CN117393782A
Carbon-supported multi-element monatomic metal catalyst
CN113258088A
Monatomic catalyst, preparation method thereof, microelectrode and preparation method and application of microelectrode
CN113786853A